2017
DOI: 10.1038/s41598-017-11380-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Micro-anatomical Structures of the Posterior Cornea with Micro-optical Coherence Tomography

Abstract: Diagnosis of corneal disease and challenges in corneal transplantation require comprehensive understanding of corneal anatomy, particularly that of the posterior cornea. Micro-optical coherence tomography (µOCT) is a potentially suitable tool to meet this need, owing to its ultrahigh isotropic spatial resolution, high image acquisition rate and depth priority scanning mode. In this study, we explored the ability of µOCT to visualize micro-anatomical structures of the posterior cornea ex vivo and in vivo using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…Recently, the first studies about corneal nerve imaging using OCT have been reported showing sub-basal nerves and occasional nerves in the stroma. [28][29][30]39 Most of these studies are proof-of-concept investigations and the image quality clearly lacks the standards of IVCM. Our article presents 3D nerve distribution, 3D nerve tracking, and a one-to-one comparison of the nerves to immunohistochemistry staining, which has not been shown in any of these articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the first studies about corneal nerve imaging using OCT have been reported showing sub-basal nerves and occasional nerves in the stroma. [28][29][30]39 Most of these studies are proof-of-concept investigations and the image quality clearly lacks the standards of IVCM. Our article presents 3D nerve distribution, 3D nerve tracking, and a one-to-one comparison of the nerves to immunohistochemistry staining, which has not been shown in any of these articles.…”
Section: Discussionmentioning
confidence: 99%
“…OCT technology advances, such as full-field OCT 26 or micro-OCT (μOCT), 27 with near isotropic 1 to 2 μm resolutions, have recently been shown to be capable of imaging small corneal nerve structure details, especially within the sub-basal plexus. 24,[28][29][30] In this article, we introduce μOCT for highresolution nerval imaging within the entire corneal stroma to validate μOCT nerve imaging as a screening tool for early PN, for example in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Micro‐OCT, which have been developed by custom modification of existing instruments, currently achieves 1 μm axial resolution at eight frames per second in tissues, making it possible to detect high‐quality cellular detail in a rapid manner; however, it is currently limited by its maximum depth of focus (150 μm) . Another laboratory has successfully custom‐built micro‐OCT to visualise rabbit endothelial cells at a cellular resolution of 1.16 μm, with individual stromal collagen bundles and endothelial cell cilia clearly identifiable when images were reconstructed en face …”
Section: Future Directionsmentioning
confidence: 99%
“…Higher NA objective lenses were employed to get lateral resolution closer to that of axial [10]. Finally, en face imaging of endothelium cells in vivo was demonstrated in animals [11,12] and humans [13]. Nevertheless, to achieve such high spatial resolution, it requires faster data acquisition to avoid significant image blur due to eye motion.…”
Section: Introductionmentioning
confidence: 99%